The data management of the language of trauma narrative communication - Chin S.W.; Chong S.T.; Musa A.B.B.; Loh K.S. (IEEE Computer Society, 2023)
Engineering education; Information management; Risk management; Analysis experts; Communication management; Community OR; Community-based studies; Content analysis; Corpus-based approaches; Self-efficacy beliefs; Word lists; Textbooks